2021
DOI: 10.4081/ija.2021.1851
|View full text |Cite
|
Sign up to set email alerts
|

Plant extracts - importance in sustainable agriculture

Abstract: Plants due to the high content of various bioactive compounds are the main raw material for production of valuable, and useful bio-products (e.g., food, cosmetics, medicines, biostimulants, biopesticides, and feed). Different plant parts, for instance: seeds, fruits, flowers, stems, leaves, and roots can be used for their manufacture. Nowadays, there is a clear need to develop new, efficient, and environmentally safe methods of stimulation of plant, growth and crop protection. Plant-based extracts are new, nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 149 publications
(317 reference statements)
0
53
0
Order By: Relevance
“…It is noted that there is an effect of the use of biostimulants on the metabolism of plants and the final quality (Colla et al, 2015 ). Plant growth, quality, tolerance to abiotic and biotic stresses, photosynthesis, and using nutrients, fertilizers, and water are able to be enhanced by plant-derived biostimulants (PDBs) by modulating plant biochemical, molecular, and physiological processes (Rouphael and Colla, 2020b ; Godlewska et al, 2021 ; Mosa et al, 2021b ). Our previous work (Hassan et al, 2021 ) showed that the most abundant phenolic compounds in Eucalyptus camaldulensis LE were pyrogallol, caffeic acid, and p -coumaric acid, in Citrus sinensis LE were syringic and ferulic acids, and in Ficus benghalensis were gallic, p-coumaric, and syringic acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that there is an effect of the use of biostimulants on the metabolism of plants and the final quality (Colla et al, 2015 ). Plant growth, quality, tolerance to abiotic and biotic stresses, photosynthesis, and using nutrients, fertilizers, and water are able to be enhanced by plant-derived biostimulants (PDBs) by modulating plant biochemical, molecular, and physiological processes (Rouphael and Colla, 2020b ; Godlewska et al, 2021 ; Mosa et al, 2021b ). Our previous work (Hassan et al, 2021 ) showed that the most abundant phenolic compounds in Eucalyptus camaldulensis LE were pyrogallol, caffeic acid, and p -coumaric acid, in Citrus sinensis LE were syringic and ferulic acids, and in Ficus benghalensis were gallic, p-coumaric, and syringic acids.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, phenolic acids and flavonoids often play the important roles in the plant's defense against disease (Sarker and Oba, 2018 ). However, the plant extracts can be considered a good source of natural antioxidants and antimicrobial in both in vitro and in vivo (Di Mola et al, 2019 ; Souri and Bakhtiarizade, 2019 ; Godlewska et al, 2021 ). The raw materials resulting from the pruning processes of Eucalyptus camaldulensis, Citrus sinensis , and Ficus benghalensis trees are readily available in high quantities in Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, EO biosynthesis was demonstrated to be strictly related to agro-climatic, soil conditions, light exposure, genetic variability, and development stage of the whole plant [11,12]. Moreover, in recent years, the application of plant extracts or biostimulants has been attempted on aromatic plants cultivation [13][14][15][16], also allowed in organic farming. Biostimulants are compounds able to enhance plant nutrition, stress tolerance, and/or plant metabolic processes in order to improve crop quality.…”
Section: Introductionmentioning
confidence: 99%
“…Using plant-based extracts, such as garlic extract as the plant biostimulant (PB) is effective to enhance the sustainability of crop protection and may increase defense responses to abiotic and biotic stresses [ [1] , [2] , [3] 4 ]. Supercritical CO 2 extraction technique and nanoscale drug delivery system (liposomes composed of plant-derived lipids) have been shown to more efficient penetration and translocation than many liquid organic solvents [ [5] , [6] 7 ].…”
Section: Data Descriptionmentioning
confidence: 99%